Handbook of Pathogens and Diseases in Cephalopods - Gestal, Camino; Pascual, Santiago; Guerra, Ángel; Fiorito, Graziano; Vieites, Juan M. (Springer International Publishing : Imprint: Springer, 2019)
The aim of this open access book is to facilitate the identification and description of the different organs as well as pathogens and diseases affecting the most representative species of cephalopods focussed on Sepia officinalis, Loligo vulgaris and Octopus vulgaris. These species are valuable 'morphotype' models and belong to the taxonomic groups Sepioidea, Myopsida and Octopoda, which include most of the species with a high market value and aquaculture potential. The study is based on photographs at macroscopic and histological level in order to illustrate the role of the most important pathogens and related diseases from the view of a pathological diagnosis. The reader is able to familiarize with functional anatomy, necropsy and general histology of adults and paralarvae, as well as with the identification of different pathogens and pathologies. This work is thus an invaluable guide for the diagnosis of cephalopod diseases. Besides including pathogens for non-European cephalopod species, it also provides a useful contribution encouraging marine pathologists, parasitologists, veterinarians and those involved in fishery sanitary assessments, aquarium maintenance and aquaculture practices aiming to increase their knowledge about the pathology of cephalopods.